Neonatal outcomes from a quasi-experimental clinical trial of Family Integrated Care versus Family-Centered Care for preterm infants in U.S. NICUs - Linda S. Franck; Caryl L. Gay; Thomas J. Hoffmann; Rebecca M. Kriz; Robin Bisgaard; Diana M. Cormier; Priscilla Joe; Brittany Lothe; Yao Sun (BMC Pediatrics, 2022)
Abstract Background Family Integrated Care (FICare) benefits preterm infants compared with Family-Centered Care (FCC), but research is lacking in United States (US) Neonatal Intensive Care Units (NICUs). The outcomes for infants of implementing FICare in the US are unknown given differences in parental leave benefits and health care delivery between the US and other countries where FICare is used. We compared preterm weight and discharge outcomes between FCC and mobile-enhanced FICare (mFICare) in the US. Methods In this quasi-experimental study, we enrolled preterm infant (≤ 33 weeks)/parent dyads from 3 NICUs into sequential cohorts: FCC or mFICare. Our primary outcome was 21-day change in weight z-scores. Our secondary outcomes were nosocomial infection, bronchopulmonary dysplasia (BPD), retinopathy of prematurity (ROP), and human milk feeding (HMF) at discharge. We used intention-to-treat analyses to examine the effect of the FCC and mFICare models overall and per protocol analyses to examine the effects of the mFICare intervention components. Findings 253 infant/parent dyads participated (141 FCC; 112 mFICare). There were no parent-related adverse events in either group. In intention-to-treat analyses, we found no group differences in weight, ROP, BPD or HMF. The FCC cohort had 2.6-times (95% CI: 1.0, 6.7) higher odds of nosocomial infection than the mFICare cohort. In per-protocol analyses, we found that infants whose parents did not receive parent mentoring or participate in rounds lost more weight relative to age-based norms (group-difference=-0.128, CI: -0.227, -0.030; group-difference=-0.084, CI: -0.154, -0.015, respectively). Infants whose parents did not participate in rounds or group education had 2.9-times (CI: 1.0, 9.1) and 3.8-times (CI: 1.2, 14.3) higher odds of nosocomial infection, respectively. Conclusion We found indications that mFICare may have direct benefits on infant outcomes such as weight gain and nosocomial infection. Future studies using implementation science designs are needed to optimize intervention delivery and determine acute and long-term infant and family outcomes. Clinical Trial Registration NCT03418870 01/02/2018.